Development of a Lateral Longitudinal Arch Evaluation Method for the Foot Using Ultrasonography: Validation With Radiography and Verification of Intrarater and Interrater Reliability - Daichi Kawamura; Takashi Komatsu; Masanobu Suto; Hikaru Narita; Yasuyuki Umezaki; Saki Takahashi; Hiroshi Shinohara (Journal of Foot and Ankle Research)
ABSTRACT Introduction The lateral longitudinal arch (LLA) is an essential structure of the foot. However, LLA evaluation methods remain underexplored compared to those of the medial longitudinal arch (MLA). This study sought to develop a method for measuring the cuboid height, the keystone of the LLA, using ultrasonography and to verify its correlation with radiography, as well as intrarater and interrater reliability. Methods This cross‐sectional study included 21 university students (14 males and seven females). The cuboid height was measured using radiography and ultrasonography. The validity of ultrasonographic measurements was assessed through correlation with radiographic measurements and Bland–Altman analysis. Intrarater and interrater reliabilities were evaluated using intraclass correlation coefficients (ICCs). Results A strong correlation was observed between cuboid heights measured using radiography and ultrasonography (r = 0.98, p < 0.01). The Bland–Altman analysis revealed a fixed bias of −0.71 mm (95% confidence interval [95% CI]: −0.96 to −0.46 mm). Intrarater and interrater reliability for ultrasonographic measurements were almost perfect, with ICCs of 0.98 and 0.99, respectively. Conclusions Cuboid height measurements using ultrasonography demonstrated high validity and reliability. This method offers a noninvasive and cost‐effective alternative to radiography, with potential clinical applications in the evaluation of LLA and related conditions such as cuboid syndrome and lateral foot injuries.